Social networks, collective organizing, and freedom of association: A qualitative participatory action research study with women migrant domestic workers in Lebanon - Abdulrahim, Sawsan; Adra, May (International Food Policy Research Institute, 2023)
Worldwide, women migrant domestic workers (WMDWs) occupy a weak position in the global economy due to intersections of gender, race, and global economic inequalities. Lebanon hosts more than 250,000 WMDWs who are recruited and employed through the infamous Kafala system that binds a worker to one employer. With Lebanon’s economic crisis, a large number of WMDWs are currently working as freelancers whereby giving and receiving support from other workers plays a crucial role in their adaptation and economic survival. This study is a component of an international evaluation of the Work in Freedom Project carried out by the International Labour Organization. It focuses on Lebanon and aims to assess the impact of the project on the ability of WMDWs in Lebanon to maintain viable social networks and organize collectively. Its main objective is to investigate the different ways in which WMDWs have maintained social networks and engaged in collective organizing efforts (at the individual, meso- and macro-levels), to improve their lives and to ensure non-exploitative work conditions.